1999
DOI: 10.1007/s002130050849
|View full text |Cite
|
Sign up to set email alerts
|

Abstinence symptoms following smoked marijuana in humans

Abstract: Symptoms of withdrawal after oral delta9-tetrahydrocannabinol (THC) administration have been reported, yet little is known about the development of dependence on smoked marijuana in humans. In a 21-day residential study, marijuana smokers (n = 12) worked on five psychomotor tasks during the day (0915-1700 hours), and in the evening engaged in recreational activities (1700-2330 hours); subjective-effects measures were completed 10 times/day. Food and beverages were available ad libitum from 0830 to 2330 hours. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
249
1
6

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 320 publications
(272 citation statements)
references
References 22 publications
(30 reference statements)
15
249
1
6
Order By: Relevance
“…These facts suggest that the increase of PPI probably cannot be explained by an acute pharmacological effect of MDMA. In the MDMA and the cannabis groups, the duration of abstinence from cannabis was considerably shorter, and it is known that there is a withdrawal syndrome lasting for several days following cessation of cannabis use (Haney et al, 1999). However, the fact that the duration of abstinence from cannabis in both groups was comparable but that an increase of PPI was shown only in the MDMA group suggests that the observed increase of PPI is not an acute effect of cannabis cessation.…”
Section: Resultsmentioning
confidence: 82%
“…These facts suggest that the increase of PPI probably cannot be explained by an acute pharmacological effect of MDMA. In the MDMA and the cannabis groups, the duration of abstinence from cannabis was considerably shorter, and it is known that there is a withdrawal syndrome lasting for several days following cessation of cannabis use (Haney et al, 1999). However, the fact that the duration of abstinence from cannabis in both groups was comparable but that an increase of PPI was shown only in the MDMA group suggests that the observed increase of PPI is not an acute effect of cannabis cessation.…”
Section: Resultsmentioning
confidence: 82%
“…Symptoms of withdrawal typically emerge after 1-2 days of abstinence, and largely resolve within 10 days (Haney et al, 1999b, Boyd et al, 2002Budney et al, 1998Budney et al, , 2001Budney et al, , 2002 Budney et al, , 2004Kouri and Pope, 2000;Stephens et al, 1993Stephens et al, , 2000. In the laboratory, marijuana withdrawal is alleviated by the resumption of marijuana smoking or by THC administration, demonstrating the pharmacological specificity of withdrawal (Haney et al, 1999b(Haney et al, , 2004Hart et al, 2002). Clinically, marijuana smokers report using marijuana to alleviate withdrawal symptoms (Budney et al, 1999), suggesting withdrawal contributes to relapse and the maintenance of marijuana use.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Both laboratory and clinical studies have demonstrated that over 50% of individuals who smoke marijuana repeatedly throughout the day, 6-7 days per week, experience a time-dependent set of withdrawal symptoms, including decreased food intake, stomach upset, restlessness, irritability, sleep difficulty, and craving. Symptoms of withdrawal typically emerge after 1-2 days of abstinence, and largely resolve within 10 days (Haney et al, 1999b, Boyd et al, 2002Budney et al, 1998Budney et al, , 2001Budney et al, , 2002Budney et al, , 2004Kouri and Pope, 2000;Stephens et al, 1993Stephens et al, , 2000. In the laboratory, marijuana withdrawal is alleviated by the resumption of marijuana smoking or by THC administration, demonstrating the pharmacological specificity of withdrawal (Haney et al, 1999b(Haney et al, , 2004Hart et al, 2002).…”
mentioning
confidence: 99%
“…Computerized psychomotor tasks (Haney et al 1999) consisted of a 3-min Digit-Symbol Substitution Task (DSST; McLeod et al 1982), a 3-min repeated-acquisition task (RA; Kelly et al 1993), a 10-min divided attention task (DAT; Miller et al 1988), a 10-min rapid information task (RIT; Wesnes and Warburton 1983), and a 3-min immediate and delayed digit-recall task (Hart et al 2001). …”
Section: Subjective-effects and Cognitive/psychomotor Batterymentioning
confidence: 99%